2006
DOI: 10.1007/s00261-006-9062-7
|View full text |Cite
|
Sign up to set email alerts
|

Aortoenteric fistula: a diagnostic dilemma

Abstract: CT can rule in the diagnosis of AEF but cannot rule it out. CT is recommended as the first-line investigation in a stable patient with suspected AEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 16 publications
2
44
0
3
Order By: Relevance
“…GI endoscopic evaluation often identifies the site of bleeding and allows directed urgent lifesaving therapy. However, the sensitivity of upper GI endoscopy in diagnosis of AEF has been reported to be only 50% (Wood et al, 2005;Hughes et al, 2007). What's worse, findings of gastritis or peptic ulcer other than AEF itself by GI endoscopy may be misleading and lead to a delayed diagnosis of AEF (Saers and Scheltinga, 2005;Mavioglu et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…GI endoscopic evaluation often identifies the site of bleeding and allows directed urgent lifesaving therapy. However, the sensitivity of upper GI endoscopy in diagnosis of AEF has been reported to be only 50% (Wood et al, 2005;Hughes et al, 2007). What's worse, findings of gastritis or peptic ulcer other than AEF itself by GI endoscopy may be misleading and lead to a delayed diagnosis of AEF (Saers and Scheltinga, 2005;Mavioglu et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Signs such as perigraft ectopic gas and intravasation of contrast into the bowel lumen or perigraft space favor the diagnosis of AEF (Perks et al, 2004). A study has compared CT scan findings with operative results and concluded that this examination had a sensitivity of 94% and a specificity of 85% in detecting AEF (Hughes et al, 2007). Multidetector CT, providing excellent image quality and enabling volume-rendered image reconstruction, is particularly useful for the diagnosis of AEF when the patient's bleeding rate is slow and when detection of the proximal part of the fistula tract might be enough for diagnosis (Ödemiş et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, diagnosis of aortoenteric fistula has been made post-mortem in half of patients because of these challenges in diagnosis. Contrastenhanced CT scanning is now the diagnostic modality of choice in this setting because of its superior sensitivity (80-90%) and specificity (100%) [5].…”
Section: Discussionmentioning
confidence: 99%
“…A negative scan in the presence a suggestive clinical picture does not rule out the diagnosis, but mandates further investigations [9]. Some authors recommend the omission of oral contrast with the abdominal CT scan in order to demonstrate contrast extravasation from the aorta into the bowel lumen [10].…”
Section: Discussionmentioning
confidence: 99%